Efficiency of Administrative Processes Through the Implementation of Digital Technology in Quality Public Services in Labuhanbatu Regency - Daulay, Ahmad Sadikin; Patwal, Anurada; Wahyudi, Bayu; Ritonga, Pirman Mulatua; Nasution, Siska Emilia Sari; Harahap, Amin (LPPPIPublishing, 2025)
This study examines the efficiency gains in public administration through the implementation of digital technology in Labuhanbatu Regency, Indonesia. Employing a qualitative descriptive approach and guided by the Technology–Organization–Environment (TOE) framework, the research explores how digital platforms, mobile services, and organizational reforms have transformed bureaucratic processes. Key findings reveal substantial improvements in processing times, cost efficiency, citizen satisfaction, and staff productivity, supported by inclusive initiatives such as the Bupati Ngantor di Desa (BUNG DESA) program. Despite infrastructural and literacy-related challenges, the government's adaptive responses—such as hybrid service delivery and targeted ICT training—have sustained the momentum of reform. The study concludes that successful digital transformation in public administration requires more than technological deployment; it demands institutional alignment, inclusive strategies, and continuous adaptation. Labuhanbatu’s experience offers valuable insights for replicating scalable, citizen-centric digital governance in other regional contexts.